On the Data of Aerodynamic Computations of Axiannular Divergent Cones - Subotovich, Valery Petrovich; Yudin, Yuriy Alexeevich; Yudin, Alexander Yuriyovich; Temchenko, Sergey Alexsandrovich (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
Comparative design investigations of axiannular divergent cones were carried out using the CFD software. Turbulence models built-in into the CFD–software were used for the computations, in particular Spalart-Allmaras (S-A), k–w Shear Stress Transport (k–w SST), V2F. The aperture angle of the external by-pass of cones varied in the range of a = 11°–36°, while the cone expansion degree varied as n = 2–4. The data of CFD computations were compared with the known experimental curve obtained by Klein and confirmed by Zariankin, which divides the plane (a–n) into two regions: unseparated flow and separated flow regions. The region above this curve represents the separated flow in the cone at any combination of parameters (a–n), and the region below this curve represents the unseparated flow. The computations done using the CFD-software for axiannular divergent cones in the studied range of the relationships of geometric parameters (a–n) showed that the use of k–ω SST and V2F models results in the flow separation in the cones situated in the unseparated flow region, which runs counter to the experimental data, and the use of the turbulence model S-A provided the unseparable flow in the region below the experimental Klein curve and resulted in the flow separation in the region below this curve. Design investigations showed that the turbulence model (Spalart-Allmaras (S-A)) provides an opportunity for the satisfactory simulation of unseparable and separable flows in the cones of this type.